Novel targeted therapies in chordoma: an update - Di Maio S; Yip S; Al Zhrani GA; Alotaibi FE; Al Turki A; Kong E; Rostomily R (Dove Medical Press, 2015)
Salvatore Di Maio,1 Stephen Yip,2 Gmaan A Al Zhrani,3,4 Fahad E Alotaibi,3,4 Abdulrahman Al Turki,3,4 Esther Kong,2 Robert C Rostomily5 1Division of Neurosurgery, Jewish General Hospital, McGill University, Montreal, QC, 2Department of Pathology and Laboratory Medicine, Vancouver General Hospital, University of British Columbia, Vancouver, BC, Canada; 3National Neuroscience Institute, Department of Neurosurgery, King Fahad Medical City, Riyadh, Saudi Arabia; 4Department of Neurology and Neurosurgery, The Montreal Neurological Institute and Hospital, McGill University Health Centre, Montreal, QC, Canada; 5Department of Neurological Surgery, University of Washington, University of Washington Medical Center, Seattle, WA, USA Abstract: Chordomas are rare, locally aggressive skull base neoplasms known for local recurrence and not-infrequent treatment failure. Current evidence supports the role of maximal safe surgical resection. In addition to open skull-base approaches, the endoscopic endonasal approach to clival chordomas has been reported with favorable albeit early results. Adjuvant radiation is prescribed following complete resection, alternatively for gross residual disease or at the time of recurrence. The modalities of adjuvant radiation therapy reported vary widely and include proton-beam, carbon-ion, fractionated photon radiotherapy, and photon and gamma-knife radiosurgery. As of now, no direct comparison is available, and high-level evidence demonstrating superiority of one modality over another is lacking. While systemic therapies have yet to form part of any first-line therapy for chordomas, a number of targeted agents have been evaluated to date that inhibit specific molecules and their respective pathways known to be implicated in chordomas. These include EGFR (erlotinib, gefitinib, lapatinib), PDGFR (imatinib), mTOR (rapamycin), and VEGF (bevacizumab). This article provides an update of the current multimodality treatment of cranial base chordomas, with an emphasis on how current understanding of molecular pathogenesis provides a framework for the development of novel targeted approaches. Keywords: chordomas, cell lines, radiation therapy, skull-base neoplasms, surgery, molecular genetics